Pairwise and incremental multi-stage alignment of metagenomes: A new proposal - Perez-Wohlfeil, Esteban; Torreño Tirado, Óscar; Trelles-Salazar, Oswaldo Rogelio (Springer, 2017)
Traditional comparisons between metagenomes are often performed using reference databases as intermediary templates from which to obtain distance metrics. However, in order to fully exploit the potential of the information contained within metagenomes, it becomes of interest to remove any intermediate agent that is prone to introduce errors or biased results. In this work, we perform an analysis over the state of the art methods and deduce that it is necessary to employ fine-grained methods in order to assess similarity between metagenomes. In addition, we propose our developed method for accurate and fast matching of reads.
Keywords: Genomas; Next generation sequencing; Metagenome comparison; Read to read comparison; Distance between metagenomes